Evaluating the Effects of an Indian Medicinal Plant, Salacia oblonga on Intestinal Morphology, Functionality and the Microbiome In Vivo (Gallus gallus). (14th June 2022) - Agarwal, Nikita; Fu, Yimin; Kolba, Nikolai; Tako, Elad
Abstract: Objectives: To assess the changes associated with the dietary consumption of alpha-glucosidase and alpha-pancreatic amylase inhibitor, Salacia oblonga water extract (SOWE) on intestinal health in-vivo. Methods: We utilized the intra-amniotic in-vivo ( Gallus gallus ) method to meet the objective. Five treatment groups viz. No Injection, 18 MΩ H2 O, 5% Inulin, 2% SOWE, and 5% SOWE were created with n∼10 for each group. On day 17 of embryonic development 1 mL of the treatments were injected into the amnion of the eggs. On day 21 (upon hatch), blood and tissue samples were collected. Hemoglobin level, mRNA expression and morphological examination of the duodenum and the cecal microbiome were conducted in the different groups. Results: The histomorphology analysis revealed a significant decrease in villi surface area, goblet cell (number and diameter) and a reduction in Paneth cell number indicating negative side effects of the extract. There was a significant reduction in inflammatory proteins at 2% SOWE but not 5% SOWE. Finally, the 16s rRNA analysis revealed significant changes in alpha diversity between the groups. Conclusions: This is the first study that assessed the effects of undigested complex carbohydrates on brush border membrane morphology, functionality, and the microbiome. The study reveals potential side effects of consuming carbohydrate enzyme inhibitors such as Salacia . Funding Sources: N/A.